Unbalanced factorials: a misunderstood analysis - Stefano Wechsler, Francisco (Pesquisa Agropecuaria Brasileira, 1998)
Few users of statistical packages are capable of analyzing unbalanced factorials properly, because introductory textbooks do not discuss this topic in detail. The present article is directed to agriculture researchers, with the purpose of clarifying the differences among several widely used programs. It shows how to test useful hypotheses about population means in models having qualitative and quantitative factors. The paper emphasizes the pitfalls of blindly applying packages without prior knowledge of the hypotheses being tested.
Keywords: statistical packages; statistical analysis; missing data